An Investigation of Syntactic Layers in Sohrab Sepehri’s Poem in Terms of Style and Tone - Marzieh Dasht bash; Ali Ahanchi (مطالعات زبانی و بلاغی)
This study aimed to examine the linguistic style (in terms of vocabulary and syntax) and Sohrab Sepehri’s thoughts and his poems have been investigated in terms of style and voice with three styles of active, passive, and reflexive. Although it’s not possible to have the exact demarcation between poetry collections of Sohrab and most of his poems contain those with the styles from previous periods, this poet has indicated passive and bonding style in his first collection entitled “Death of Colors” that depicts the outside world of his own. The collections entitled “The Life of Dreams, Debris of Sun, The East of Sorrow, The Water’s Footsteps, Passenger, and The Green Volume” that are based on his introspective and personal poetic intuition, have active and reflexive styles. In his last collection entitled “We Nothing, We Look” that is influenced by the awareness of disease, he has been involved in a romantic grief and by having lofty but vague language, his style becomes inactive and stationary and his voice changes to a quiet and passive mood.